Hyperglycaemia and ABO Blood Groups: An Investigative Analysis among Young Adults of Hyderabad, Sindh, Pakistan: ABO Blood Groups and Hyperglycaemia in Young Adults - Shaikh, Shakil Ahmed; Memon, Salma Farukh; Muhammad, Areej; Laghari, Hira; Memon, Naila; Laghari, Keenjher Rani; Laghari, Zulfiqar Ali (Pakistan Journal of Health Sciences, 2025)
Serious health problems include nerve damage, renal failure, and an increased risk of cardiovascular disease can result from chronic hyperglycemia. Objective: To investigate the relationship between hyperglycemia and ABO blood types in young adults from Hyderabad, Sindh. Methods: 582 randomly selected healthy individuals, 281 females and 301 males, aged 18 to 40, were recruited from various institutions for this cross-sectional study, which took place between January 2, 2021, and January 31, 2022. The data was gathered using the basic random approach. All participants gave their informed consent prior to recruitment. Descriptive statistics including mean, standard deviation, and frequency distributions were computed using the Chi-square test. Data collection was analyzed using SPSS version 20.0. Results: This study included 582 participants. In male individuals, the mean age was 27.83 ± 5.478, and in females, 22.27 ± 4.730. The mean BMI was 25.81 ± 5.08 in males and 24.00 ±4.90 in females. The 207 B blood group individuals were found to be obese, comprising 112 males and 95 females, followed by 195 individuals with blood group O, 128 individuals with blood group A, and 52 individuals with blood group AB. People who are Rh-positive and have blood group B were shown to be more likely to experience elevated hyperglycemia. Conclusion: Blood group B and Rh-positive status may be linked to higher hyperglycemia risk in young adults from Hyderabad, suggesting blood typing as a potential screening tool.